2018
DOI: 10.1007/s10915-018-0723-9
|View full text |Cite
|
Sign up to set email alerts
|

An Improved High Order Finite Difference Method for Non-conforming Grid Interfaces for the Wave Equation

Abstract: This paper presents an extension of a recently developed high order finite difference method for the wave equation on a grid with nonconforming interfaces. The stability proof of the existing methods relies on the interpolation operators being norm-contracting, which is satisfied by the second and fourth order operators, but not by the sixth order operator. We construct new penalty terms to impose interface conditions such that the stability proof does not require the normcontracting condition. As a consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The new schemes are similar to those derived in [26], but with truncation errors of order p−1 instead of p−2. Since numerical experiments in [26] showed global convergence rates of order p + 1, one may expect the new schemes to converge with rate p + 2, which is supported by numerical experiments in section 7. Figure 1: Non-zero elements for an example pair of interpolation operators (p = 2).…”
Section: The Second Order Wave Equationmentioning
confidence: 91%
See 1 more Smart Citation
“…The new schemes are similar to those derived in [26], but with truncation errors of order p−1 instead of p−2. Since numerical experiments in [26] showed global convergence rates of order p + 1, one may expect the new schemes to converge with rate p + 2, which is supported by numerical experiments in section 7. Figure 1: Non-zero elements for an example pair of interpolation operators (p = 2).…”
Section: The Second Order Wave Equationmentioning
confidence: 91%
“…The approach has since been extended to the Schrödinger equation [20], the second order wave equation [29], and the advection-diffusion equation [12]. For equations with second derivatives in space, it has been observed that the SATs at the non-conforming interfaces worsen the largest local truncation error, and hence the global convergence rate, by one order, as compared to conforming interfaces [12,19,26]. The obvious remedy would have been to increase the order of accuracy of the interpolation operators, but [13] showed that this is impossible because the order of the interpolation operators is bounded from above by the order of the quadrature rule associated with every SBP operator [9].…”
Section: Introductionmentioning
confidence: 99%
“…The second choice of SATs uses four penalty terms [28], which has a better stability property for problems with curved interfaces. The method was improved further in [1] from the accuracy perspective when non-periodic boundary conditions are used in the x-direction.…”
Section: The Sbp-sat Methodsmentioning
confidence: 99%
“…However, the scheme is not accurate when dealing with complex geometries such as the characterization of the coastlines during the simulation [18]. To deal with these limitations, refined mesh approaches are applied to increase the resolution of certain areas of interest [34]. Nevertheless, there are still some problems facing this approach when the waves are reflected from the coastline outside the finer mesh as such waves are not well resolved.…”
Section: Introductionmentioning
confidence: 99%